Critical thinking ability of 3rd year radiography students - Tracey Pieterse; Heather Lawrence; Hesta Friedrich-Nel (AOSIS, 2016)
Background: Developing the critical thinking skills of student radiographers is imperative in an era of rapidly advancing technology. The status of the students' ability to demonstrate critical thinking skills needed to be explored for the Department of Radiography at a comprehensive university to determine if a more explicit curriculum was needed to facilitate these skills. Aim: The aim of this article is to present results of a study conducted to determine the critical thinking ability of 3rd year radiography students at a Comprehensive University in South Africa. Method: The research study used a descriptive exploratory design to collect both quantitative and qualitative data. Quantitative data was collected by scoring the participants ability to think critically when answering clinical scenarios posed in the form of vignettes given to the students under assessment conditions. The qualitative data was generated by in-depth field notes made inductively by the researcher. Results: The findings of this study indicated that the majority of participants demonstrated a minimal ability to think critically. Conclusion: The study results imply that in order to improve critical thinking skills of student radiographers, there is a need for curriculum adjustment, to nurture and encourage these skills. It is recommended that facilitators adopt methods to integrate these skills in the curriculum.